Methode zur Entwicklung hybrider Technologie- und Innovationsstrategien am Beispiel des Automobils - Rath, M.

Protokollverarbeitung mit integrierten Multiprozessoren in drahtlosen Ad-hoc-Netzwerken - Grünewald, M.

Theoretische und experimentelle Untersuchungen zum Einsatz gepulster Halbleiterlichtquellen in der Kraftfahrzeugbeleuchtung - Strauss, Steffen

Systematik der Materialflussplanung in der frühen Phase der Produktionssystementwicklung - Zeidler, Christian

A Method for the intelligent Authoring of 3D Animations for Traimimg and Maintenance - Parisi, Salvatore

Methods to Exploit Reconfigurable Fabrics - Dittmann, Florian

Programm-, Ressourcen- und Prozessoptimierung als Bestandteile der Anpassungsplanung von spanenden Fertigungssystemen in der Fließfertigung - Tonigold, C.

A Predictive Potential Field Concept for Shared Vehicle Guidance - Brandt, Thorsten

7. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung - Gausemeier, Jürgen; Grafe, Michael

A Methodology for the Identification of Technology Indicators - Chang, Hua

Proceedings of the 4th Workshop on Object-oriented Modeling of Embedded Real-Time Systems - Gehrke, Matthias; Giese, Holger; Stroop, Joachim

Entwicklung einer Methodik zur Online-Qualitätsüberwachung des Ultraschall-Drahtbondprozesses mittels integrierter Mikrosensorik - Brökelmann, Michael

Architektur und Entwurf dynamisch rekonfigurierbarer FPGA-Systeme - Kettelhoit, Boris

Concepts for the development of a generic Multi-Level Test Bench covering different areas of applications - Zambaldi, Martin

8. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung

How pre- and postnatal risk factors modify the effect of rapid weight gain in infancy and early childhood on subsequent fat mass development: results from the Multicenter Allergy Study 90. - Karaolis-Danckert, N; Buyken, Anette; Kulig, M; Kroke, A; Forster, J; Kamin, W; Schuster, A; Hornberg, C; Keil, T; Bergmann, RL; Wahn, U; Lau, S (Am J Clin Nutr)

Entscheidungsorientierte Planung unscharfer Erfolge von KMU in Supply Chains - Betz, Stefan (Entscheidungsprobleme im Supply Chain Management - Quantitative Lösungsansätze für den Mittelstand)

Analyse des Bullwhip-Effekts in einer Supply Chain von KMU - Betz, Stefan (Entscheidungsprobleme im Supply Chain Management - Quantitative Lösungsansätze für den Mittelstand)

A comprehensive approach in modeling Lagrangian particle deposition in turbulent boundary layers - Horn, M.; Schmid, Hans-Joachim (Powder Technology)
Modeling of particle deposition on adjacent walls is a key issue in various applications like separation or transport processes. The present paper focuses on the modeling of turbophoretic deposition of particles in the micron size range. The first step is to evaluate the important range where turbophoresis plays an important role in comparison to other mechanisms e.g. gravity or electrostatic separation. The disadvantages of commonly used models will be analyzed and overcome by implementing a more sophisticated approach considering damping of turbulent fluctuations in the wall-boundary layer. In contrast to previous work, commonly used turbulence models are applied to solve the mean flow field of the examples under consideration. The results will show a good prediction of particle deposition in comparison to experimental values [B.Y.H. Liu, J.K. Agarwal, Experimental observation of aerosol deposition in turbulent flow, Aerosol. Sci. 5 (1974) 145–155.] by using the advanced model.

Kolmogorov Complexity Theory over the Reals - Ziegler, Martin; Koolen, Wouter M. (arXiv:0802.2027)
Kolmogorov Complexity constitutes an integral part of computability theory, information theory, and computational complexity theory -- in the discrete setting of bits and Turing machines. Over real numbers, on the other hand, the BSS-machine (aka real-RAM) has been established as a major model of computation. This real realm has turned out to exhibit natural counterparts to many notions and results in classical complexity and recursion theory; although usually with considerably different proofs. The present work investigates similarities and differences between discrete and real Kolmogorov Complexity as introduced by Montana and Pardo (1998).